Noise Addition Strategies for Differential Privacy in Stochastic Gradient Descent - Lu, Kangjie (Transactions on Computer Science and Intelligent Systems Research, 2024)
Differential privacy technology is more and more widely used in the field of machine learning, especially in the gradient descent algorithm (SGD). Protecting data privacy by adding noise has become a hot topic of research. This paper reviews the noise addition strategy of differential privacy SGD from multiple dimensions, including adjustment based on noise distribution, adjustment based on gradient norm, adjustment based on privacy budget, and method based on model architecture. Each strategy has different performances in terms of privacy protection level, model performance loss and computational complexity. This article compares and analyzes these differences in detail, aiming to provide valuable reference for researchers and practitioners. This article also discusses how to combine federal learning and differential privacy technology to protect data privacy more efficiently in a secure multi-party computing (MPC) environment. Through the review of this article, we can see the wide application of differential privacy in machine learning and deep learning and its importance in the field of privacy protection. At the same time, we also show the direction and challenges of future research.